2019
DOI: 10.2147/idr.s209971
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence, risk and genetic characteristics of drug-resistant tuberculosis in a tertiary care tuberculosis hospital in China</p>

Abstract: Objectives To explore the prevalence, risk and genetic characteristics of drug-resistant tuberculosis (TB) from a tertiary care TB hospital in China. Patients and methods We carried out a retrospective study including isolates from 189 patients with pulmonary TB at Fuzhou Pulmonary Hospital. All isolates from these patients were subjected to drug susceptibility testing and genotyping. For drug-resistant isolates, DNA sequencing was used to investigate mutations in 12 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“… 34 We also observed that the Beijing genotype exhibited a significantly higher risk for developing MDR-TB compared to non-Beijing genotype, suggesting that Beijing genotype be responsible for the spread and emergence of MDR-TB in this region. As reported in previous studies, 35 , 36 retreated patients in this study were also found with high risk for developing MDR-TB, stressing the importance of early diagnosis, and timely, long-term and standardized medication, especially among patients treated within the hospital system in this region.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 34 We also observed that the Beijing genotype exhibited a significantly higher risk for developing MDR-TB compared to non-Beijing genotype, suggesting that Beijing genotype be responsible for the spread and emergence of MDR-TB in this region. As reported in previous studies, 35 , 36 retreated patients in this study were also found with high risk for developing MDR-TB, stressing the importance of early diagnosis, and timely, long-term and standardized medication, especially among patients treated within the hospital system in this region.…”
Section: Discussionsupporting
confidence: 83%
“… 6 , 42 There was no isolate carried rrs mutation combined with rpsL mutation in this study, suggesting that mutations in rrs and rpsL genes were mutually exclusive. Mutations in rrs and rpsL genes accounted for 68.6% STR resistance, higher than the data from the tertiary care tuberculosis hospital in China 35 and Mexico, 43 but lower than that from other regions, 44 , 45 indicating that there were regional differences in the mutations associated with STR resistance and additional resistance mechanisms correlated with STR resistance, such as gidB which was reported to contribute 2.4% to 37.5% STR resistance. 42 , 44 , 46–48 …”
Section: Discussionmentioning
confidence: 56%